2012
DOI: 10.1111/j.1601-183x.2012.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxytocin and oxytocin receptor gene variants in childhood‐onset aggression

Abstract: Aggressive antisocial behaviours are the most common reasons why adolescents are referred to mental health clinics. Antisocial behaviours are costly in social and financial terms. The aetiology of aggressive behaviours is unknown but growing evidence suggests it is heritable, and certain genetic variants have been implicated as contributing factors. The purpose of this study was to determine whether genes regulating the hormone oxytocin (OXT) were associated with aggressive antisocial behaviour. The case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 45 publications
3
88
1
2
Order By: Relevance
“…A lower-than-normal plasma OT level in ASD subjects (Modahl et al, 1998;Andari et al, 2010; and an association of ASD with OXTR (Wu et al, 2005;Jacob et al, 2007;Lerer et al, 2008;Liu et al, 2010) further support a link between OT and ASD, although some inconsistency in association between ASD and OXTR was also recognized (Tansey et al, 2010;Campbell et al, 2011). Furthermore, several pioneering studies have suggested improvements in autistic behavioral and cognitive characteristics following administration of OT.…”
Section: Oxytocin and Autistic Social Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lower-than-normal plasma OT level in ASD subjects (Modahl et al, 1998;Andari et al, 2010; and an association of ASD with OXTR (Wu et al, 2005;Jacob et al, 2007;Lerer et al, 2008;Liu et al, 2010) further support a link between OT and ASD, although some inconsistency in association between ASD and OXTR was also recognized (Tansey et al, 2010;Campbell et al, 2011). Furthermore, several pioneering studies have suggested improvements in autistic behavioral and cognitive characteristics following administration of OT.…”
Section: Oxytocin and Autistic Social Dysfunctionmentioning
confidence: 99%
“…In addition, several studies have examined limbic brain structure in the context of rs2254298, a genetic polymorphism that has been repeatedly linked to ASD, although there has been heterogeneity regarding the risk-associated allele in populations of different ethnicity (Wu et al, 2005;Jacob et al, 2007;Liu et al, 2010). The first imaging genetics study in a large sample of healthy Japanese adults (Inoue et al, 2010) used manual tracing methods to derive amygdala volumes, and examined the relationship of these measures to seven SNPs and one haplotype block in OXTR linked to ASD.…”
Section: Neurogenetic Effects Of Social Risk Variants In Oxtr On Limbmentioning
confidence: 99%
See 1 more Smart Citation
“…The OTR and OT are involved in memory and learning, stress regulation and anxiety, and aggressive, sexual and maternal behaviors (e.g. Argiolas 1992, Malik et al 2012, Ebner et al 2013. Moreover, the OTR is involved in thermoregulation and brain development (Gimpl & Fahrenholz 2001, Kasahara et al 2013).…”
Section: R68 Reviewmentioning
confidence: 99%
“…Özellikle, düşük oksitosin beyin omurilik sıvısı (28), oksitosin reseptör geninin (OXTR) işlevsel polimorfizmlerinde ortaya çıkan kayıp (29,30) ve oksitosin reseptör geni promoterinde (transkripsiyonu başlatan kısım) epigenetik susturma (metilasyon) genç erkeklerde dürtüsel ve saldırgan mizaçla, kişiler arası şiddet ve acımasız-duygusuz özelliklerle ilişkili bulunmuştur (31). Benzer şekilde hayvan çalışmaları alanındaki veriler, sosyal davranışsal yanıt düzenlenmesinde santral oksitosinerjik kontrolünün önemini güçlendirmiştir.…”
Section: öZunclassified